A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard and its preparation process

Through the secondary sintering process, Al4O4C is synthesized in situ in Al2O3-C skateboard, which solves the problem of easy oxidation and poor hydration resistance at high temperatures, and achieves excellent oxidation, hydration resistance and mechanical properties, extends service life and reduces resource waste.

CN119751032APending Publication Date: 2025-04-04YIXING REFRACTORY MATERIAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411104039.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing Al2O3-C skateboards are easy to oxidize at high temperatures, have poor hydration resistance, and are complex in preparation process, high cost and short service life, resulting in waste of resources.

Method used

The secondary sintering process is adopted to generate the Al4C3 transition phase through the first medium-temperature treatment. In the second high-temperature sintering, Al4O4C is synthesized in situ as a binding phase through the solid solution reaction between Al4C3 and Al2O3, which improves the anti-oxidation, hydration and high-temperature performance of the skateboard.

Benefits of technology

It achieves excellent hydration, oxidation and mechanical properties of the skateboard, extends its service life, reduces production costs, and does not produce impurities after use, and in theory, it can achieve unlimited resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751032A_ABST
    Figure CN119751032A_ABST
Patent Text Reader

Abstract

Metal Al is added to the Al2O3-C slide plate, and an Al4C3 transition phase is generated during the first medium-temperature treatment. After the second high-temperature treatment and sintering, Al4C3 is solid-solution-absorbed by Al2O3 to form an Al4O4C-bonded Al2O3-C slide plate in situ. The slide plate of the present invention has excellent anti-hydration, anti-oxidation, high-temperature performance and use effect. The material will not introduce new impurities when it fails after service, and can be recycled indefinitely.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an Al 4 O 4 C-bound Al 2 O 3 -C slide plate and its preparation process belong to the field of inorganic non-metallic materials, high temperature ceramics and refractory materials. Background Art

[0002] The slide plate is a functional component that directly controls the flow and velocity of molten steel and determines the sliding nozzle system. During use, the slide plate is repeatedly subjected to erosion, chemical erosion and strong thermal shock of molten steel. In order to meet the precise flow control function, the slide plate must have excellent properties such as high temperature resistance, high strength, good corrosion resistance, good thermal shock resistance, high oxidation resistance and low creep. 2 O 3 -C skateboard or Al 2 O 3 -ZrO 2 -C skateboard is the mainstream skateboard used by large and medium-sized steel enterprises in China. 2 O 3 -C skateboard anti-oxidation performance, usually add single Al, Si and non-oxide SiC, B 4 C acts as an antioxidant. It preferentially combines with oxygen to react and produce a dense oxide layer or ceramic reinforcement (bonding) phase, filling the pores, making the material denser, and preventing the oxidizing gas from further diffusing into the skateboard, thus achieving the purpose of "sacrificing" the antioxidant to protect the carbon from being oxidized. At the same time, it can also improve the mechanical properties of the material. Different antioxidants have different reactivity at different temperatures. You can choose a variety of antioxidants to protect carbon-containing refractory materials in different temperature ranges and improve the material's antioxidant properties. For example, Si powder has a low reactivity and is generally used during high-temperature sintering. Although Si powder can react to produce SiO at high temperatures, 2 、Si 3 N 4 、SiC can improve Al 2 O 3 -C skateboard mechanical properties and oxidation resistance, but the liquid phase mullite at high temperature will make the high temperature performance of the material worse, and SiO 2 It will react with steel slag to produce low melting products such as calcium feldspar, which is not conducive to the high temperature use of the skateboard, so the amount of Si added must be controlled. For example, Al powder can react at medium and low temperatures to produce AlN and Al 4 C 3 Although the reinforcement phase can increase the volume density of the material, AlN, Al 4 C 3 It is very easy to get wet, which can cause the skateboard to be damaged in a humid environment.

[0003] Preparation of Al 2 O 3 -C skateboard or Al 2 O 3 -ZrO 2 -C skateboard production process includes three processes: unfired, medium temperature treatment, and high temperature firing. Unfired skateboard production process is simple, short production process, and low cost, but because the binder resin of unfired skateboard is heated and burned by high temperature molten steel during service, it is carbonized and coked, which easily causes the skateboard to deform. In order to overcome the disadvantage of deformation of unfired skateboards, unfired skateboards are heated to a medium temperature of 600~1000℃ before service, so that the resin is coked and carbonized, but the skateboards produced by the medium temperature treatment process produce easily hydrated Al 4 C 3 The high temperature fired skateboard is a skateboard that has been fired at a temperature above 1350℃. In addition to the ingredients, mixing, and molding processes, the fired skateboard also needs carbon or nitrogen protection firing, oil immersion, polishing, etc. The production cycle is long, the equipment is complex, there are many process control points, and the cost is high.

[0004] The study found that Al 4 C 3 and Al 2 O 3 There exists a stable ternary compound Al in a binary system 4 O 4 C, Al 4 O 4 C has high strength, maintains chemical stability at high temperatures, does not undergo hydrolysis, and is not easily oxidized. Therefore, it has potential application prospects in the field of refractory materials. 4 O 4 The synthesis of C is not well studied, the synthesis mechanism is not clear, and different reaction conditions and different reaction processes have different effects on Al 4 O 4 C has a great influence on the synthesis of Al 4 O 4 The preparation of C is difficult, and there is no mature product available on the market so far.

[0005] In addition, the service life of the skateboard is limited. After sliding several times, it is replaced and taken offline, becoming solid waste after service. In the previous production process, various antioxidants, additives, combustion aids and other substances were often added to improve the skateboard's anti-oxidation, anti-corrosion, and thermal shock resistance. As a result, the waste after service has too many impurities, making it difficult to recycle and reuse, and can only be downgraded for use, resulting in a huge waste of resources.

[0006] In order to solve the above technical difficulties, the present invention adopts a secondary sintering process, only adding metal Al to Al2 O 3 -C skateboard or Al 2 O 3 -ZrO 2 -C slide plate, Al is produced during the first medium temperature treatment 4 C 3 Transition phase, during the secondary high temperature sintering, through Al 4 C 3 By Al 2 O 3 Absorbing the solid solution in-situ synthesis mechanism, preparing Al with excellent high temperature performance and anti-oxidation and anti-hydration properties 4 O 4 C acts as a bonding phase to improve Al 2 O 3 -C Slide refractory materials have anti-hydration, anti-oxidation and high temperature properties. Summary of the invention

[0007] A kind of Al of the present invention 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 30-45 parts of corundum with a particle size of 2-1 mm; (2) 15-25 parts of plate-shaped corundum with a particle size of 1-0.088 mm; (3) 3-7 parts of plate-shaped corundum with a particle size of 0.045-0.020 mm; (4) 3 to 10 parts of flake graphite with a particle size of 0.18 to 0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 0-10 parts of zirconium corundum with a particle size of 0.18-0.15 mm, wherein the zirconium corundum Al 2 O 3 +ZrO 2 ≥99%, of which ZrO 2 ≥25%; (6) 8-15 parts of aluminum powder with a particle size of 0.074-0.045 mm; (7) 1-3 parts of carbon black with a particle size of 0.045-0.020 mm; (8) α-Al with a particle size of 2~1μm 2 O 3 3~10 parts of micro powder; (9) 4-6 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing (97-99) parts of a phenolic resin and (1-3) parts of a polycarboxylic acid.

[0008] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18~0.15mm, zirconium corundum with a particle size of 0.18~0.15mm, aluminum powder with a particle size of 0.074~0.045mm, carbon black with a particle size of 0.045~0.020mm, plate corundum with a particle size of 0.044~0.020mm, α-Al with a particle size of 2~1μm 2 O 3 The fine powder and micro powder are strongly premixed for 15 to 20 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 2-3 minutes, add 2-3 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 3-5 minutes, then add the remaining pre-configured composite resin binder in 3-5 times, and mix and grind vigorously to form a mixture. The effective mixing and grinding time is 20-40 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: keep the material in a sealed container for 24 to 36 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 48 to 72 hours, and then drying at 200 to 300 °C for 24 to 72 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: for the first heat treatment, the temperature is raised to 750-950°C at a heating rate of 5-10°C / min and kept at this temperature for 6-8 hours; after the first heating and keeping at this temperature, the temperature is raised to 1450-1500°C at a heating rate of 1-3°C / min and kept at this temperature for 3-6 hours for the second heat treatment sintering; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0009] The technical features of the present invention are: (1) The skateboard of the present invention has good strength consistency and low sensitivity to temperature. The resin bonding has high strength at low temperature; the metal-aluminum carbide-carbon mesh bonding is formed at medium temperature; the Al2O3 bond is formed after high temperature sintering. 4 O 4 C ceramic bonding, both maintain high strength; (2) The slide plate of the present invention is subjected to two heat treatments to form Al in situ 4 O 4 The mechanism of C-ceramic bonding is as follows: During the first medium-temperature treatment, the metal Al liquid flows to the carbon edge wrapped in alumina. The Al liquid has high reaction activity and can fully contact with C and adhere to Al. 2 O 3 The surrounding C reacts to form Al 4 C 3Fill the pores to make the slide dense, the reaction formula is 4Al(l)+3C(s)= Al 4 C 3 (s), the volume expansion caused by the reaction further densifies the material, and some Al powder may also be oxidized to form Al 2 O 3 A dense protective layer is formed to prevent the gas from further diffusing inward, making the slide plate have good oxidation resistance. During the second high-temperature sintering, Al 4 C 3 and Al 2 O 3 Solid solution reaction occurs in Al 2 O 3 In-situ formation of Al 4 O 4 C bridge connection, the reaction formula is Al 4 C 3 (s)+4 Al 2 O 3 (s)=3Al 4 O 4 C(s), columnar Al 4 O 4 C penetrates the pores to form bridges and toughen the material, thus improving the mechanical properties of the material. Figure 1 shown.

[0010] (3) Al of the present invention 2 O 3 -C skateboard raw materials are simple, only single metal aluminum Al, oxide Al 2 O 3 , and carbon C and carbon derivative resin, the resin is coked and carbonized at medium temperature to form an intermediate transition phase Al 4 C 3 , after high temperature sintering, Al 4 O 4 C. The skateboard has excellent anti-hydration, anti-oxidation and mechanical properties. After long-term use, Al 4 O 4 C protects C from oxidation by sacrificing itself, thus improving the oxidation resistance and service life of the skateboard. 4 O 4 C(s)+O 2 (g) = 2Al 2 O 3 (s) + C (s), and the reaction formula in the local reducing atmosphere is Al 4 O 4 C(s)+2CO(g)=2Al 2 O 3 (s)+3C(s), finally Al 4 O4 C is consumed and converted into Al 2 O 3 and C, the material becomes only Al oxide after failure 2 O 3 And the solid waste emissions of the original raw material components of carbon C. Because no more impurities are produced after use, theoretically, unlimited resource recycling can be achieved, achieving zero solid waste emissions.

[0011] The beneficial effects of the present invention are as follows: (1) The raw material of the skateboard is simple, containing only Al, Al 2 O 3 and C, low cost; (2) by controlling the secondary heat treatment process, a skateboard with excellent oxidation resistance, hydration resistance and mechanical properties is obtained; (3) the skateboard has a long service life and can slide continuously for more than 5 times; (4) the skateboard does not produce new impurities after use and can be recycled indefinitely. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 In-situ formation of Al for secondary heat treatment 4 O 4 C-bound Al 2 O 3 -C schematic diagram of the slide reaction mechanism; Figure 2 This is a SEM image of the holes left behind when the metal Al melts into liquid and infiltrates around carbon in Example 1; Figure 3 The transition state Al is generated after the first heat treatment in Example 1. 4 C 3 SEM images of Figure 4 The final Al is generated after the second heat treatment of Example 1 4 O 4 SEM image of C; Figure 5 The final state of Al in Example 1 2 O 3 Columnar Al 4 O 4 SEM image of C-bridge connection; Figure 6 is the XRD phase diffraction spectrum of the final state of the embodiment, wherein 1 # , 2 # , 3 # , 4 # , 5 # They are respectively Example 1, Example 2, Example 3, Example 4, and Example 5; Figure 7 The material of Example 1 fails after service. 4 O 4C is converted into granular Al 2 O 3 SEM image of . DETAILED DESCRIPTION Example

[0013] A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 30 parts of corundum with a particle size of 2~1mm; (2) 25 parts of plate-shaped corundum with a particle size of 1 to 0.088 mm; (3) 3 parts of plate-shaped corundum with a particle size of 0.045~0.020mm; (4) 10 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 15 parts of aluminum powder with a particle size of 0.074~0.045mm; (6) 1 part of carbon black with a particle size of 0.045-0.020 mm; (7) α-Al with a particle size of 2~1μm 2 O 3 Micro powder 10 parts; (8) 6 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing 99 parts of a phenolic resin and 1 part of a polycarboxylic acid.

[0014] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18-0.15 mm, aluminum powder with a particle size of 0.074-0.045 mm, carbon black with a particle size of 0.045-0.020 mm, plate-shaped corundum with a particle size of 0.044-0.020 mm, and α-Al with a particle size of 2-1 μm. 2 O 3 The fine powder and micro powder are strongly premixed for 20 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 2 minutes, add 3 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 3 minutes, then add the remaining pre-configured composite resin binder in 5 times, and mix and grind vigorously to form a mixture. The effective time of mixing and grinding is 40 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: sealed material trapping for 36 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 72 hours, and then drying at 300°C for 24 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: the first heat treatment is to increase the temperature to 750°C at a heating rate of 5°C / min and keep it at that temperature for 8 hours; after the first heating and keeping at that temperature, the second heat treatment sintering is performed at a heating rate of 1°C / min to 1450°C and keep it at that temperature for 6 hours; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0015] Table 1 lists the performance test results of Example 1, indicating that the strength of the slide plate at low, medium and high temperatures remains relatively stable: the compressive strength after thermosetting is 134MPa, the compressive strength after primary heat treatment is 122MPa, and the compressive strength of the final state after secondary sintering is 146MPa. The room temperature flexural strength of the final state after secondary sintering is 38MPa, and the high temperature (1400℃×0.5h) flexural strength of the final state after secondary sintering is 30MPa. It shows that the strength of the slide plate is very low in sensitivity to temperature. The slide plate has excellent thermal shock resistance, 1100℃×0.5h, and the thermal shock resistance (times) is broken after 11 cycles. The slide plate has excellent oxidation resistance 1400℃×0.5h, and the oxidized area is only 11.6%. Therefore, the comprehensive use effect of the slide plate is good. In a certain state steel plant, the casting temperature is 1580~1620℃, and the molten steel is not treated with calcium. After 5 consecutive slides, there is only a roughening phenomenon.

[0016] Table 1 A kind of Al of the present invention 4 O 4 C-bound Al 2 O 3 -C Skateboard Example Performance List Example

[0017] A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 45 parts of corundum with a particle size of 2 to 1 mm; (2) 15 parts of plate-shaped corundum with a particle size of 1 to 0.088 mm; (3) 7 parts of plate-shaped corundum with a particle size of 0.045~0.020mm; (4) 3 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 8 parts of aluminum powder with a particle size of 0.074~0.045mm; (6) 3 parts of carbon black with a particle size of 0.045~0.020mm; (7) α-Al with a particle size of 2~1μm 2 O 3 3 parts of micro powder; (8) 4 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing 98 parts of a phenolic resin and 2 parts of a polycarboxylic acid.

[0018] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18-0.15 mm, aluminum powder with a particle size of 0.074-0.045 mm, carbon black with a particle size of 0.045-0.020 mm, plate-shaped corundum with a particle size of 0.045-0.020 mm, and α-Al with a particle size of 2-1 μm. 2 O 3 The fine powder and micro powder are vigorously premixed for 15 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry-mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 3 minutes, add 2 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 5 minutes, then add the remaining pre-configured composite resin binder in 3 times, and mix and grind vigorously to form a mixture. The effective time for mixing and grinding is 20 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: sealed material trapping for 24 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 48 hours, and then drying at 200°C for 72 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: the first heat treatment is to increase the temperature to 950°C at a heating rate of 10°C / min and keep it at that temperature for 6 hours; after the first heating and keeping at that temperature, the second heat treatment sintering is performed at a heating rate of 3°C / min to 1500°C and keep it at that temperature for 3 hours; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0019] Table 1 lists the performance test results of Example 2, indicating that the strength of the skateboard at low, medium and high temperatures remains relatively stable: the compressive strength after thermosetting is 140MPa, the compressive strength after one heat treatment is 128MPa, and the compressive strength of the final state after secondary sintering is 143MPa. The room temperature flexural strength of the final state after secondary sintering is 33MPa, and the high temperature (1400℃×0.5h) flexural strength of the final state after secondary sintering is 26MPa. It shows that the strength of the skateboard is very low in sensitivity to temperature. The skateboard has excellent thermal shock resistance, 1100℃×0.5h, and large cracks appear after 11 cycles of thermal shock resistance (times). The skateboard has excellent oxidation resistance, 1400℃×0.5h, and the oxidized area is only 11.4%. Therefore, the comprehensive use effect of the slide plate is good. In a certain Shan Steel Plant, the casting temperature is 1550~1650℃, the molten steel is treated with calcium, and slight cracks appear after 5 consecutive sliding. A certain Han Steel Plant's 100-ton oxygen top-blown ladle, casting silicon steel, slides 5 times in a row and slight cracks appear. Example

[0020] A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 38 parts of corundum with a particle size of 2 to 1 mm; (2) 20 parts of plate-shaped corundum with a particle size of 1 to 0.088 mm; (3) 5 parts of plate-shaped corundum with a particle size of 0.045~0.020mm; (4) 7 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 11 parts of aluminum powder with a particle size of 0.074~0.045mm; (6) 2 parts of carbon black with a particle size of 0.045~0.020mm; (7) α-Al with a particle size of 2~1μm 2 O 3 7 parts of micro powder; (8) 5 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing 97 parts of a phenolic resin and 3 parts of a polycarboxylic acid.

[0021] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18-0.15 mm, aluminum powder with a particle size of 0.074-0.045 mm, carbon black with a particle size of 0.045-0.020 mm, plate-shaped corundum with a particle size of 0.045-0.020 mm, and α-Al with a particle size of 2-1 μm. 2 O 3The fine powder and micro powder are strongly premixed for 18 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry-mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 3 minutes, add 3 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 4 minutes, then add the remaining pre-configured composite resin binder in 4 times, and mix and grind vigorously to form a mixture. The effective time for mixing and grinding is 30 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: sealed material trapping for 36 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 72 hours, and then drying at 250°C for 48 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: in the first heat treatment, the temperature is raised to 850°C at a heating rate of 5°C / min and kept at this temperature for 7 hours; after the first heating and keeping at this temperature, the temperature is raised to 1500°C at a heating rate of 1-3°C / min and kept at this temperature for 5 hours for the second heat treatment sintering; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0022] Table 1 lists the performance test results of Example 3, indicating that the strength of the skateboard at low, medium and high temperatures remains relatively stable: the compressive strength after thermosetting is 138MPa, the compressive strength after one heat treatment is 126MPa, and the compressive strength of the final state after secondary sintering is 145MPa. The room temperature flexural strength of the final state after secondary sintering is 35MPa, and the high temperature (1400℃×0.5h) flexural strength of the final state after secondary sintering is 28MPa. It shows that the strength of the skateboard is very sensitive to temperature. The skateboard has excellent thermal shock resistance, 1100℃×0.5h, and large cracks appear after 11 cycles of thermal shock resistance (times). The skateboard has excellent oxidation resistance 1400℃×0.5h, and the oxidized area is only 11.4%. Therefore, the comprehensive use effect of the skateboard is good. In a certain mountain steel plant, the casting temperature is 1550~1650℃, and the molten steel is treated with calcium. After 5 consecutive slides, slight cracks appear. Example

[0023] A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 38 parts of corundum with a particle size of 2 to 1 mm; (2) 20 parts of plate-shaped corundum with a particle size of 1 to 0.088 mm; (3) 5 parts of plate-shaped corundum with a particle size of 0.045~0.020mm; (4) 7 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 5 parts of zirconium corundum with a particle size of 0.18-0.15 mm, wherein the zirconium corundum Al 2 O 3 +ZrO 2 ≥99%, of which ZrO 2 ≥25%; (6) 11 parts of aluminum powder with a particle size of 0.074~0.045mm; (7) 2 parts of carbon black with a particle size of 0.045~0.020mm; (8) α-Al with a particle size of 2~1μm 2 O 3 7 parts of micro powder; (9) 5 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing 97 parts of a phenolic resin and 3 parts of a polycarboxylic acid.

[0024] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18~0.15mm, zirconium corundum with a particle size of 0.18~0.15mm, aluminum powder with a particle size of 0.074~0.045mm, carbon black with a particle size of 0.045~0.020mm, plate corundum with a particle size of 0.045~0.020mm, α-Al with a particle size of 2~1μm 2 O 3 The fine powder and micro powder are strongly premixed for 18 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry-mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 3 minutes, add 3 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 4 minutes, then add the remaining pre-configured composite resin binder in 4 times, and mix and grind vigorously to form a mixture. The effective time for mixing and grinding is 30 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: sealed material trapping for 36 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 72 hours, and then drying at 250°C for 48 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: in the first heat treatment, the temperature is raised to 850°C at a heating rate of 5°C / min and kept at this temperature for 7 hours; after the first heating and keeping at this temperature, the temperature is raised to 1500°C at a heating rate of 1-3°C / min and kept at this temperature for 5 hours for the second heat treatment sintering; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0025] Table 1 lists the performance test results of Example 4, indicating that the strength of the skateboard at low, medium and high temperatures remains relatively stable: the compressive strength after thermosetting is 139MPa, the compressive strength after one heat treatment is 127MPa, and the compressive strength of the final state after secondary sintering is 148MPa. The room temperature flexural strength of the final state after secondary sintering is 36MPa, and the high temperature (1400℃×0.5h) flexural strength of the final state after secondary sintering is 28MPa. It shows that the strength of the skateboard is very low in sensitivity to temperature. The skateboard has excellent thermal shock resistance, 1100℃×0.5h, and large cracks appear after 11 cycles of thermal shock resistance (times). The skateboard has excellent oxidation resistance 1400℃×0.5h, and the oxidized area is only 11.3%. Therefore, the comprehensive use effect of the skateboard is good. In a certain mountain steel plant, the casting temperature is 1550~1650℃, and the molten steel is treated with calcium. After 5 consecutive slides, slight cracks appear.

[0026] Compared with Example 3, Example 4 adds 5 parts of zirconium corundum. Since the introduction of zirconium corundum can improve the thermal shock resistance and corrosion resistance of the slide plate, the use effect is slightly better than that of Example 3. Example

[0027] A kind of Al 4 O 4 C-bound Al 2 O 3 -C skateboard, by weight, the formula is as follows: (1) 38 parts of corundum with a particle size of 2 to 1 mm; (2) 20 parts of plate-shaped corundum with a particle size of 1 to 0.088 mm; (3) 5 parts of plate-shaped corundum with a particle size of 0.045~0.020mm; (4) 7 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; (5) 10 parts of zirconium corundum with a particle size of 0.18-0.15 mm, wherein the zirconium corundum Al 2 O 3 +ZrO 2 ≥99%, of which ZrO 2 ≥25%; (6) 11 parts of aluminum powder with a particle size of 0.074~0.045mm; (7) 2 parts of carbon black with a particle size of 0.045~0.020mm; (8) α-Al with a particle size of 2~1μm 2 O 3 7 parts of micro powder; (9) 5 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing 97 parts of a phenolic resin and 3 parts of a polycarboxylic acid.

[0028] The specific process of the present invention comprises the following eight steps: (1) Premixing of fine powders: flake graphite with a particle size of 0.18~0.15mm, zirconium corundum with a particle size of 0.18~0.15mm, aluminum powder with a particle size of 0.074~0.045mm, carbon black with a particle size of 0.045~0.020mm, plate corundum with a particle size of 0.045~0.020mm, α-Al with a particle size of 2~1μm 2 O 3 The fine powder and micro powder are strongly premixed for 18 minutes to obtain premixed fine powder; (2) Mixing and grinding: dry-mix corundum with a particle size of 2-1 mm and plate-shaped corundum with a particle size of 1-0.088 mm for 3 minutes, add 3 parts of composite resin binder, add the pre-mixed fine powder and mix and grind for 4 minutes, then add the remaining pre-configured composite resin binder in 4 times, and mix and grind vigorously to form a mixture. The effective time for mixing and grinding is 30 minutes; (3) Screening: After the mixed material is discharged, it is screened with a 5 mm sieve to remove large agglomerates; (4) Material trapping: sealed material trapping for 36 hours; (5) Molding, machine pressing; (6) Drying and curing: natural drying for 72 hours, and then drying at 250°C for 48 hours; (7) Heat treatment: After drying and solidification, heat treatment is performed twice in a carbon-buried atmosphere: in the first heat treatment, the temperature is raised to 850°C at a heating rate of 5°C / min and kept at this temperature for 7 hours; after the first heating and keeping at this temperature, the temperature is raised to 1500°C at a heating rate of 1-3°C / min and kept at this temperature for 5 hours for the second heat treatment sintering; (8) After heat treatment, the product is naturally cooled, hooped, ground, shelled, and the working surface of the skateboard is coated with paint and packaged.

[0029] Table 1 lists the performance test results of Example 5, indicating that the strength of the skateboard at low, medium and high temperatures remains relatively stable: the compressive strength after thermosetting is 130MPa, the compressive strength after one heat treatment is 128MPa, and the compressive strength of the final state after secondary sintering is 150MPa. The room temperature flexural strength of the final state after secondary sintering is 37MPa, and the high temperature (1400℃×0.5h) flexural strength of the final state after secondary sintering is 29MPa. It shows that the strength of the skateboard is very low in sensitivity to temperature. The skateboard has excellent thermal shock resistance, 1100℃×0.5h, and large cracks appear after 12 cycles of thermal shock resistance (times). The skateboard has excellent oxidation resistance 1400℃×0.5h, and the oxidized area is only 11.3%. Therefore, the comprehensive use effect of the skateboard is good. In a certain mountain steel plant, the casting temperature is 1550~1650℃, and the molten steel is treated with calcium. After 5 consecutive slides, slight cracks appear.

[0030] Compared with Example 3, Example 4 adds 10 parts of zirconium corundum. Since the introduction of zirconium corundum can improve the thermal shock resistance and corrosion resistance of the slide plate, the use effect is slightly better than that of Example 3.

Claims

1. An Al4O4C-bonded Al2O3-C slide plate of the present invention has the following formula in parts by weight: 30~45 parts of corundum with a particle size of 2~1mm; 15-25 parts of plate-shaped corundum with a particle size of 1-0.088 mm; 15-25 parts of plate-shaped corundum with a particle size of 0.045-0.020 mm; 3-10 parts of flake graphite with a particle size of 0.18-0.15 mm, wherein the carbon content of the flake graphite is ≥ 95%; 0-10 parts of zirconium corundum with a particle size of 0.18-0.15 mm, wherein the zirconium corundum Al2O3+ZrO2≥99%, wherein ZrO2≥25%; 8-15 parts of aluminum powder with a particle size of 0.074-0.045 mm; 1-3 parts of carbon black with a particle size of 0.045-0.020 mm; 3~10 parts of α-Al2O3 powder with a particle size of 2~1μm; 4-6 parts of a composite resin binder, wherein the composite resin binder is prepared by mixing (97-99) parts of a phenolic resin and (1-3) parts of a polycarboxylic acid; The specific process includes the following eight steps: The first step is to premix fine powders, and vigorously premix flake graphite with a particle size of 0.18-0.15 mm, zirconium corundum with a particle size of 0.18-0.15 mm, aluminum powder with a particle size of 0.074-0.045 mm, carbon black with a particle size of 0.045-0.020 mm, plate corundum with a particle size of 0.045-0.020 mm, and α-Al2O3 with a particle size of 2-1 μm. Fine powder and micro powder are obtained for a premixing time of 15-20 minutes; The second step is mixing and grinding. Dry-mix the corundum with a particle size of 2-1 mm and the plate-shaped corundum with a particle size of 1-0.088 mm for 2-3 minutes, add 2-3 parts of the composite resin binder, add the pre-mixed fine powder and mix and grind for 3-5 minutes, then add the remaining pre-configured composite resin binder in 3-5 times, and mix and grind vigorously to form a mixture. The effective time of mixing and grinding is 20-40 minutes. The third step is screening. After the mixed material is discharged, it is screened with a 5mm sieve to remove large agglomerates; The fourth step is to trap the material in a sealed manner for 24 to 36 hours; The fifth step is molding, machine pressing molding; The sixth step is drying and curing. After natural drying for 48 to 72 hours, it is dried at 200 to 300°C for 24 to 72 hours. The seventh step is heat treatment. After drying and solidification, two heat treatments are carried out in a carbon-buried atmosphere: the first heat treatment is to increase the temperature to 750-950°C at a heating rate of 5-10°C / min and keep it warm for 6-8h; after the first heating and heat preservation, the temperature is increased to 1450-1500°C at a heating rate of 1-3°C / min and kept warm for 3-6h for the second heat treatment sintering; The eighth step is natural cooling, hooping, grinding, shell bonding, coating of the working surface of the skateboard and packaging after heat treatment.